Review of the Medical Student Performance Evaluation: analysis of the end-users' perspective across the specialties. Issue 1 (1st January 2021) - Bird, Jeffrey B.; Friedman, Karen A.; Arayssi, Thurayya; Olvet, Doreen M.; Conigliaro, Rosemarie L.; Brenner, Judith M.
ABSTRACT: The Medical Student Performance Evaluation (MSPE) is an important tool of communication used by program directors to make decisions in the residency application process. To understand the perspective and usage of the MSPE across multiple medical specialties now and in anticipation of the planned changes in USMLE Step 1 score-reporting. A survey instrument including quantitative and qualitative measures was developed and piloted. The final survey was distributed to residency programs across 28 specialties in 2020 via the main contact on the ACGME listserv. Of the 28 specialties surveyed, at least one response was received from 26 (93%). Eight percent of all programs (364/4675) responded to the survey, with most respondents being program directors. Usage of the MSPE varied among specialties. Approximately 1/3 of end-users stated that the MSPE is very or extremely influential in their initial screening process. Slightly less than half agreed or strongly agreed that they trust the information to be an accurate representation of applicants, though slightly more than half agree that the MSPE will become more influential once USMLE Step 1 becomes pass/fail. Professionalism was rated as the most important component and noteworthy characteristics among the least important in the decision-making process. Performance in the internal medicine clerkship was rated as the most influential while neurology and psychiatry performances were rated as less influential. Overwhelmingly, respondents suggested that including comparative performance and/or class rank would make the MSPE more useful once USMLE Step 1 becomes pass/fail. MSPE end-users across a variety of specialties utilize this complex document in different ways and value it differentially in their decision-making processes. Despite this, continued mistrust of the MSPE persists. A better understanding of end-users' perceptions of the MSPE offers the UME community an opportunity to transform the MSPE into a highly valued, trusted document of communication.